Late stillbirth due to listeriosis - Antonio Segado-Arenas; Lidia Atienza-Cuevas; José Roman Broullón-Molanes; Moisés Rodríguez-González; Simón Pedro Lubián-López (University of São Paulo, 2018)
Listeriosis is a sporadic infectious disease, which affects high-risk populations, such as the elderly, pregnant women, newborns, and immunocompromised patients. During pregnancy, listeriosis usually presents like a mild non-specific infection, but it may be responsible for fetal loss, preterm labor, early onset neonatal sepsis, and neonatal death. We report the case of a late stillbirth secondary to maternal chorioamnionitis. Listeria monocytogenes was isolated from the amniotic fluid and the fetal pleural fluid. The fetal autopsy revealed a disseminated inflammatory response with multi-organ involvement. This case illustrates the importance of the prevention and the diagnosis of listeriosis during gestation and may help us to understand the physiopathology of fetal loss due to listeriosis.